Cultural features influencing eating, overweight, and obesity in the Roma people of South Bohemia - Olišarová, Věra; Tóthová, Valérie; Bártlová, Sylva; Dolák, František; Kajanová, Alena; Nováková, Dita; Prokešová, Radka; Šedová, Lenka (MDPI AG, 2018)
This article describes the important cultural specifics that impact on treatment of overweight and obesity for the Roma people of South Bohemia. Methods: Data on health and nutrition were collected using a semi-structured interview of 302 Roma adults (quantitative phase). A further 25 participants received in-depth interviews regarding their eating and lifestyle habits and perceptions about obesity and overweight (qualitative phase). Height and weight were measured with calibrated scales and stadiometer. Qualitative data were analyzed with the “grounded theory” method. Results: The participants reported a relatively high consumption of high-sugar drinks and foods compared to fruits and vegetables. Lifestyle factors increasing risk of overweight identified from the qualitative interview included unemployment, socially isolating housing, poor transport, poverty, inactivity, tobacco smoking, and for women weight gain after childbirth. Also identified was the need for better health literacy. Conclusions: Effective health education may help to address risk factors for overweight and obesity in Roma peoples. Other measures include improved socioeconomic status and housing security, and improved health literacy of the Roma people.
Vliv kulturních zvyklostí na výživu, nadváhu a obezitu u Romů v Jihočeském kraji
Keywords: the Roma; nurse; overweight; obesity; health education; lifestyle factors; nutrition; cultural features; Rom; sestra; nadváha; obezita; zdravotní edukace; faktory životního stylu; výživa; kulturní zvyklosti